Peritoneal Dialysis in Infants and Children After Open Heart Surgery - Jen-Chung Chien; Be-Tau Hwang; Zen-Chung Weng; Laura Chun-Chang Meng; Pi-Chang Lee (Elsevier, 2009)
Infants and children who undergo surgical repair of complex congenital heart diseases are prone to developing renal dysfunction. The purpose of this study was to investigate the risk factors associated with prolonged peritoneal dialysis (PD) and the mortality of pediatric patients with acute renal failure (ARF) after open heart surgery. Methods: From June 1999 to May 2007, a total of 542 children underwent open heart surgery for congenital heart disease. Fifteen (2.8%) experienced ARF and seven (1.3%) required PD. The clinical and laboratory variables were compared between the survivor and non-survivor groups of ARF patients that needed PD. Results: The non-survivors (n = 3, 43%) had a longer cardiopulmonary bypass time (154 ± 21 vs. 111 ± 8 minutes, p = 0.012) and longer aorta clamping time (92 ± 40 vs. 66 ± 15 minutes, p = 0.010) than the survivors (n = 4, 57%). Before the PD, the pH and base excess of the arterial blood gas analysis in the survivors was much higher than that non-survivors (7.30 ± 0.04 vs. 7.16 ± 0.10, p = 0.039; −5.15 ± 3.13 vs. −12.07 ± 2.9 mmol/L, p = 0.031). Furthermore, the survivors had a shorter interval between the onset of ARF and the day the PD was begun (1.2 ± 0.4 vs. 4.3 ± 1.2 days, p = 0.001), and shorter duration of PD (6.6 ± 2.7 vs. 13.0 ± 3.5 days, p= 0.036) than non-survivors. Conclusion: Early intervention with PD is a safe and effective method for managing patients with ARF after open heart surgery. The cardiopulmonary bypass and aortic clamping duration, time of initiating PD, duration of the PD, sepsis, and relative complications may predict the prognosis of these patients.